Voluntary risk disclosures of Islamic financial institutions: the role of AAOIFI standards implementation - Romlah Jaffar,; Al Sheikh, Warda; Mohamat Sabri Hassan,; Maizatulakma Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The implementation of the Accounting and Auditing Organization for Islamic Financial Institutions standards (AAOIFI) can improve the risk disclosure practices of Islamic financial institutions (IFIs) that eventually will reduce information asymmetry and improve the legitimacy. However, its role in the presence of Risk Management Committee (RMC) and Sharia Supervisory Board (SSB) with voluntary risk disclosure (VRD) has not been investigated before. Therefore, this study investigates the role of AAOIFI standards implementation on the relationship between RMC and SSB effectiveness with VRD. The sample consists of 167 firm-year observations of IFIs listed on Saudi Arabian Stock Exchange (TADAWUL) from 2013 to 2017. Data of the study are collected from IFIs annual reports. Agency and signalling theories explain the effect of RMC and SSB on VRD. Additionally, legitimacy theory predicts the moderating role of AAOIFI standards. The results show that the effectiveness of RMC and SSB have a positive effect on the level of VRD. However, the AAOIFI standards implementation does not strengthen the relationship between RMC and SSB effectiveness with the level of VRD. This insignificant finding could be due to the non-mandatory nature of AAOIFI standards implementation in Saudi Arabia. The results of the study enhance the current understanding of the importance of effective RMC and SSB to improve the risk reporting that can reduce information asymmetry and strengthen legitimacy amongst IFIs. The findings are also useful to regulatory bodies and policymakers to develop the policies and regulations that could influence the disclosure and transparent reporting by listed companies.